(untitled) (Scientiae Studia, 2008)
This article presents some relationships between Gilles Personne de Roberval´s mechanics and Marin Mersenne´s acoustics, showing, for one side, how the first provides important foundations to understand the relationship between the motion of a string and the tension to which it is submitted and, for another side, in what sense acoustics contributes to mechanical studies.